Fighting Heroes: The Core Values of the Xia Tradition in Early China - Albert Dalia (Universidad de León, 2012)
The core values of China's famed wuxia (heroic fiction) literature and cinema developed in response to the chaos and warfare of the Warring States Period (475-221 B.C.E.). In English, probably the best commercial source of information on this topic is Professor James J.Y. Liu's book, The Chinese Knight-Errant (1967), which unfortunately is out of print. This article is based on that book, along with the author's academic and literary work on the East Asian hero. These heroic values appear to be rooted in individualism, which would seem to contradict the region's vaunted sense of group cohesiveness.